PENGARUH IKLAN WEBSERIES PONDAN “CITA RASA RAISA” TERHADAP BRAND AWARENESS VIEWERS - Damanik, Shekina Hanna; Cristin, Pratiwi; Herwandito, Seto (Linimasa : Jurnal Ilmu Komunikasi, 2024)
Advertising is part of the communication strategy to market the object or service presented by the company which is useful as a medium of reminder for consumers of the products advertised by the advertiser. Along with the growth of PONDAN, many emerging new premix flour so PONDAN still need to increase brand awareness. The author is interested to see the influence of advertising webseries PONDAN "taste of Raisa" on brand Awareness audience. The purpose of this study was to examine the impact of PONDAN web series ads titled "Cita Rasa Raisa" on brand awareness among viewers. The method used is a simple regression analysis with a quantitative approach. The results showed that the dimension of attention has the greatest influence is the proportion of respondents who strongly agree with 67.9%. Hypothesis testing shows that PONDAN online advertising has a positive effect on people's brand awareness, with an R value of 0.711 showing a positive correlation. This is in line with the principle of communication that the sender's message is conveyed effectively to the communicator in the form of brand awareness. Thus, it can be concluded that the advertisement of the transvestite webseries "taste of Raisa" affects the audience's brand awareness.